2016
DOI: 10.1371/journal.ppat.1006111
|View full text |Cite
|
Sign up to set email alerts
|

Within Host Evolution Selects for a Dominant Genotype of Mycobacterium tuberculosis while T Cells Increase Pathogen Genetic Diversity

Abstract: Molecular epidemiological assessments, drug treatment optimization, and development of immunological interventions all depend on understanding pathogen adaptation and genetic variation, which differ for specific pathogens. Mycobacterium tuberculosis is an exceptionally successful human pathogen, yet beyond knowledge that this bacterium has low overall genomic variation but acquires drug resistance mutations, little is known of the factors that drive its population genomic characteristics. Here, we compared the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…Thus, we next considered these results in light of published patient data. Recent publications have suggested that NGS technologies could facilitate personalized treatment in TB patients, allowing for improved outcomes (Copin et al . 2016; Cancino-Muñoz et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we next considered these results in light of published patient data. Recent publications have suggested that NGS technologies could facilitate personalized treatment in TB patients, allowing for improved outcomes (Copin et al . 2016; Cancino-Muñoz et al .…”
Section: Resultsmentioning
confidence: 99%
“…1993)) have similarly been discussed within these contexts (Pepperell et al . 2010; Copin et al . 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The majority (82%) of these absent epitopes are contained in 6 antigenic proteins encoded in RD1 and RD2 deleted in BCG strains. These and related studies further suggested that epitope sequence variation in BCG potentially affects human T cell recognition that could result in ineffective priming of the host immune system [16,17,[50][51][52].…”
Section: The Current Clinical Tb Vaccine Pipelinementioning
confidence: 89%
“…The stocks of M. tuberculosis H37Rv, H37Rv:Δ fbpB (Ag85B-null), 4334, and M. africanum 1182 used in our laboratory and for these studies have been previously described (19, 42-44). The M. tuberculosis HN878 strain was obtained from BEI Resources.…”
Section: Methodsmentioning
confidence: 99%